Fabrication of PLGA Based Tissue Engineering Scaffolds via Photocuring and Salt Leaching Techniques - ÇAKMAKÇI, EMRAH; KAYAMAN APOHAN, NİLHAN (TAYLOR & FRANCIS AS, 2013)
The authors aimed to prepare UV curable porous scaffolds via photo curing and salt leaching techniques. A poly ( -hydroxy ester) based urethane acrylate oligomer was synthesized and a photocurable acrylic based formulation was prepared. Salt particles were introduced to the formulation, which was then poured into cylindrical molds and cured under UV irradiation. Porous scaffolds were obtained after salt leaching. 3T3 cells seeded on the UV cured scaffolds and it was found that cells were well spread on the collagen modified scaffold surface. It can be concluded that the scaffolds provided an effective physical support that allows cell adhesion and proliferation.
Keywords: Photocuring; PLGA; salt leaching; tissue engineering; POROGEN; BONE